2022
DOI: 10.1155/2022/9377334
|View full text |Cite|
|
Sign up to set email alerts
|

Application Value of Combined Detection of Anti-β2-GPI, ACL, and Lupus Anticoagulant in the Diagnosis of Patients with Antiphospholipid Syndrome

Abstract: Objective. To investigate the application value of combined detection of anti-beta 2-glycoprotein I antibody (anti-β2-GPI), anti-cardiolipin antibody (ACL), and lupus anticoagulant (LA) in the diagnosis of patients with antiphospholipid syndrome (APS). Methods. 30 APS patients in our hospital between Jan. 2020 and Jan. 2021 were chosen as the experimental group, and 30 healthy persons with normal physical examination during the same period were selected as the control group The anti-β2-GPI and ACL indexes of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%